2016
DOI: 10.1016/j.ympev.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Revision of widespread red squirrels (genus: Tamiasciurus) highlights the complexity of speciation within North American forests

Abstract: Integration of molecular methods, ecological modeling, and statistical hypothesis testing are increasing our understanding of differentiation within species and phylogenetic relationships among species by revealing environmental connections to evolutionary processes. Within mammals, novel diversity is being discovered and characterized as more complete geographic sampling is coupled with newer multi-disciplinary approaches. North American red squirrels exemplify a forest obligate genus whose species are monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 107 publications
0
44
1
Order By: Relevance
“…Mt Graham red squirrels are an isolated, endangered subspecies restricted to the Pinaleñ o Mountains, in southeastern Arizona, USA, and represent the southernmost population of red squirrels in North America [27] (figure 1). Recent genetic analyses suggest that southwestern Tamiasciurus belong to a separate species T. fremonti [28], further distinguishing Mt Graham red squirrels genetically from other red squirrel populations in which NHPI has been investigated. The Mt Graham red squirrel is uniquely suited to study NHPI and its influence on habitat use and selection for many reasons: (i) Mt Graham red squirrels (hereafter red squirrels) are intensively monitored via mark-recapture, radiotelemetry, and population surveys, hence many individuals of known age are followed during the period when both dispersal and settlement are known to occur, (ii) recent analyses of nuclear and mitochondrial DNA indicate that little genetic variation exists, with mean inter-individual relatedness ¼ 0.75 [27,29], which may allow us to more adequately disentangle the influence of genetics or NHPI on inter-individual differences in habitat selection observed in the field [12], (iii) recent disturbance events including insect infestation beginning in 1996 [30] and subsequent wildfires in 1996 and 2004 [31] have altered forest composition and continuity, in some areas leaving structure intact, but substantially reducing living biomass, and (iv) despite high mortality and reduced reproductive success in insect damaged spruce-fir forest, red squirrel settlement cues appear to remain unchanged, suggesting a potential ecological trap for individuals that settle there [16,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Mt Graham red squirrels are an isolated, endangered subspecies restricted to the Pinaleñ o Mountains, in southeastern Arizona, USA, and represent the southernmost population of red squirrels in North America [27] (figure 1). Recent genetic analyses suggest that southwestern Tamiasciurus belong to a separate species T. fremonti [28], further distinguishing Mt Graham red squirrels genetically from other red squirrel populations in which NHPI has been investigated. The Mt Graham red squirrel is uniquely suited to study NHPI and its influence on habitat use and selection for many reasons: (i) Mt Graham red squirrels (hereafter red squirrels) are intensively monitored via mark-recapture, radiotelemetry, and population surveys, hence many individuals of known age are followed during the period when both dispersal and settlement are known to occur, (ii) recent analyses of nuclear and mitochondrial DNA indicate that little genetic variation exists, with mean inter-individual relatedness ¼ 0.75 [27,29], which may allow us to more adequately disentangle the influence of genetics or NHPI on inter-individual differences in habitat selection observed in the field [12], (iii) recent disturbance events including insect infestation beginning in 1996 [30] and subsequent wildfires in 1996 and 2004 [31] have altered forest composition and continuity, in some areas leaving structure intact, but substantially reducing living biomass, and (iv) despite high mortality and reduced reproductive success in insect damaged spruce-fir forest, red squirrel settlement cues appear to remain unchanged, suggesting a potential ecological trap for individuals that settle there [16,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on our phylogenetic inferences and species delimitation analyses, as well as available information in the literature (e.g. phenotypic and karyotypic data, analyses of geographic variation and previous phylogenetic and species delimitation analyses; [1,2,21,[23][24][25][26][27]), we adopted a more conservative approach and recognized the initial set of 43 OTUs as putative species of Sciurini ( Figure 6), all of which are treated as distinct terminal taxa in the following analyses. From those 43 OTUs, 37 represent described species recognized as valid by the latest taxonomic hypothesis comprising those taxa ([1], [2], [43]; but granatensis includes richmondi and alfari includes venustulus), while six are putative additional species to be described or revalidated ("species 1-3", aestuans "a-b", and ignitus-currently considered as a subspecies of pucherani by [2], but meriting specific status as per our results).…”
Section: Species Monophyly and Species Recognitionmentioning
confidence: 99%
“…Considering the possible methodological weaknesses mentioned above and the shortfalls of our sampling of taxa and data, we evaluate the results of our molecular species delimitation analyses with special caution in some situations. For example, the genus Tamiasciurus was recently extensively revised through molecular analyses (including mitochondrial and nuclear genes) and ecological niche modeling, with over 250 specimens examined from throughout the distribution of the genus [23]. These authors found evidence for the recognition of T. douglassi and T. hudsonicus as valid species.…”
Section: Comments On Species Recognition and Noveltiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1), and it is estimated that MGRS have been isolated for at least 10,000 years following post-Pleistocene glacial retreat (Harris 1990). MGRS are morphologically, vocally, and genetically distinct from their nearest conspecific (Koprowski et al 2005;Fitak et al 2013), and have recently been assigned to a new species of southwestern Tamiasciurus (T. fremonti) based upon systematics and niche-based divergences (Hope et al 2016). Despite being a relatively small mammal (200-250 g) (Steele 1998), MGRS move substantial distances during natal dispersal, distances that are far greater than reported for other red squirrel populations (Merrick and Koprowski 2016a).…”
Section: Study Organismmentioning
confidence: 99%